Hubungan Antara Penyulit Persalinan Dengan Kejadian Sectio Caesarea di Rumah Sakit Khusus Daerah Ibu Dan Anak Pertiwi Makassar - Astiani Astiani; Eha Sumantri; Rahmawati Rahmawati; Sainuddin Sainuddin; Muhammad Saleh (Communication and Social Dinamics (CSD), 2020)
Background: Women should be informed that a planned caesarean section leads to a smaller reduction in perinatal mortality compared to a planned vaginal breech birth. Any decision to have a Caesarean section needs to be balanced with the potential adverse consequences that may result from this. Methods: This research used analytical survey method. The population in this study were all women who had been treated at the Makassar Regional Mother and Child Hospital for the period January - April 2019 totaling 259 people. The data analysis used was descriptive analysis with percentage, bivariate analysis with Chi- square test and Multivariate analysis with logistic regression. Result: There was a relationship between contraction abnormalities and caesarean section with p-value of 0.003, there was a relationship between birth path abnormalities and caesarean section, with p-value of 0.004, there was a relationship between fetal location abnormalities and caesarean section, with p-value of 0.003, and there was a relationship between placental abnormalities and caesarean section, with p-value of 0.002, the risk factors for labor with an occasional caesarean section with contraction abnormalities (OR adjusted: 5.024; 95% CI: 1.511- 16.710), placental abnormalities (adjusted OR: 3.996; 95% CI: 1,143- 13,970). Conclusion: Contraction abnormality variable is the most dominant variable associated with the incidence of caesarean section in RSKD for mothers and children pertiwi Makassar s is placental abnormalities because it has the largest OR value.. Keywords: complicated labor; sectio caesarea